Endoscopic versus open surgical management of bile duct stones (Journal of Dhaka National Medical College & Hospital, 2014)
Bile duct stones is one of common  cause of obstructive jaundice.Endoscopic procedure less expensive open surgical approach. Cross sectional study was done.Objectives to compare the therapeutic outcome of ERCP in comparison to open bile duct exploration.The study was carried out in the department of surgery in BSMMU from 1st july 2007 to june 2009.Methods : A total of 50 patients with choledocholithiasis were evaluated in the department of surgery, BSMMU . Initial evaluation of the patients by history, clinical examination were performed and associated with or without increased alkaline phosphates, serum bilirubin, SGOT, SGPT, and prothrombin time and common bile duct stones or a CBD diameter dilated or not on ultrasonography.  Patient’s prothrombin time and control time difference more than 3 were excluded due to avoid massive bleeding in ERCP and they were treated accordingly to perform ERCP. Baseline laboratory investigation  were done for each patient as pre-requisite of ERCP or open cholidocholithotomy.Results: out of 50 patients 11 were male and 14 were female in group I. In group II 12 were male and 13 were female. The male female ratio 1:2. Post-operative jaundice was found 1 (4%)  in group I, wound infection 3(12%) in group II.Conclusion : ERCP is a safe and highly accurate diagnostic procedure in experience hands. Therapeutic potential associated with cholangiography includes endoscopic sphingterotomy, stone removal from bile ducts and placement of various kinds of stents to bridge benign and malignant stenosis. So, the management of bile duct stones and the palliation of malignant biliary stricture have largely shifted from surgery to endoscopy.J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 51-56